La participación docente en la toma de decisiones desde la visión micropolítica - Obando Castillo, Gustavo (2008)
The teacher is the one who experiences close by the problematic of the schoolsystem, the one who makes decisions, modifies or sabotages the school plans, theone who transmits the vision of the school or makes it difficult, among othersaspects; all which reveal the teacher as the key for maintaining alive the educativeorganizations. For this reason, it is important that the teacher participates in theschools with consciousness taking part of the decision making process.However, in a micropolitical context, the participation can occur in a complexway and not always be open to discussion, making use of a variety of strategies(like alliances, rumors and comments) so that the different groups and individualsreach their interests, those that are not necessarily aligned with the school ones orother groups’ interests.